Optimized and secured data collection and recovery for IoT applications - Kumar, M. Tanooj; Praveena, T.; Lakshman, T.; Sai Krishna, M. (International Journal of Engineering and Technology, 2018)
This paper proposes a new compressive sensing based method for data collection and recovery related to IoT based systems. It performs data capturing, its compression and encryption at the same time, transmission, storage and its recovery. The measurement matrix, used in compressive sensing, is generated based on the user private key and is utilized for encrypting the captured data. Basis Pursuit is used for reconstruction of the data. The results shows that it is very suitable for the IoT based applications by considering data security, transmission cost and storage cost.Â Â